2016
DOI: 10.1155/2016/4218989
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CAF-Related Proteins Is Associated with Histologic Grade of Breast Phyllodes Tumor

Abstract: Purpose. The purpose of this study was to investigate the expression of cancer-associated fibroblast- (CAF-) related proteins and the implications in breast phyllodes tumor (PT). Methods. Tissue microarrays of 194 PT cases (151 benign PT, 27 borderline PT, and 16 malignant PT) were constructed. We performed immunohistochemical staining for CAF-related proteins (podoplanin, prolyl 4-hydroxylase, FAPα, S100A4, PDGFR α/β, and NG2) and analyzed the results according to clinicopathologic parameters. Results. Expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In a xenograft mouse model of lung cancer, PDGFRα has been shown to promote the recruitment of fibroblasts to the tumor infiltration front. PDGFRα/β high CAFs have also been linked to lymph node metastasis and lymphovascular invasion in ovarian cancer [ 84 ] and pancreatic cancer [ 48 ] and lead to poorer prognosis in breast cancer [ 78 ], ovarian cancer [ 84 ], pancreatic cancer [ 48 ], and lobular breast tumors [ 85 ]. Inhibition of PDGFR signaling can restrain cervical cancer angiogenesis and cell proliferation [ 86 ].…”
Section: Caf Markers With Cancer Promotionmentioning
confidence: 99%
“…In a xenograft mouse model of lung cancer, PDGFRα has been shown to promote the recruitment of fibroblasts to the tumor infiltration front. PDGFRα/β high CAFs have also been linked to lymph node metastasis and lymphovascular invasion in ovarian cancer [ 84 ] and pancreatic cancer [ 48 ] and lead to poorer prognosis in breast cancer [ 78 ], ovarian cancer [ 84 ], pancreatic cancer [ 48 ], and lobular breast tumors [ 85 ]. Inhibition of PDGFR signaling can restrain cervical cancer angiogenesis and cell proliferation [ 86 ].…”
Section: Caf Markers With Cancer Promotionmentioning
confidence: 99%
“…For example, a cytokine storm induced by M2 macrophages upon new-adjuvant treatment in ovarian cancer promotes tumor growth and progression ( 44 ). As for specific upregulated cytokines, we found that PDGFRB, a molecular marker of CAFs ( 45 ), was highly expressed in C1 ( P < 0.001). CXCL10, upregulated in C2 ( P < 0.001), is a pro-inflammatory cytokine involved in the chemotactic recruitment of macrophages, natural killer cells, dendritic cells, and active T lymphocytes to tumor cells ( 46 ).…”
Section: Resultsmentioning
confidence: 96%
“…Among the 8,056 studies, 290 passed the screening based on title and abstract among which 27 studies were selected for systematic review and meta-analysis ( Amornsupak et al, 2017 ; Ariga et al, 2001 ; Busch et al, 2012 ; Cai et al, 2017 ; Egeland et al., 2017 ; Eiro et al, 2019 ; Eiró et al., 2015 ; Gonzalez et al, 2009 ; Jung, Lee & Koo, 2015 ; Kim, Lee & Koo, 2016 ; Martinez et al, 2015 ; Min et al, 2013 ; Muchlińska et al., 2022 ; Park, Jung & Koo, 2016 ; Park, Kim & Koo, 2015 ; Paulsson et al, 2009 ; Pula et al, 2011 ; Pula et al, 2013a ; Pula et al, 2013b ; Schoppmann et al, 2012 ; Strell et al, 2019 ; Surowiak et al, 2007 ; Tanaka et al, 2021 ; Yamashita et al, 2012 ; Yang et al, 2017 ; Zhang et al, 2008 ; Zhou et al, 2018 ) ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%